Aborto legal de gravidez decorrente de violência sexual : representações sociais de médicos/as - Puls, Ivana Sessak (2024)
Pregnancy resulting from sexual violence is a serious public health issue in Brazil, and legal abortion is one of its possibilities. Access to this right comes up against barriers such as blaming the victim for the violence and doctors refusing to perform abortions, claiming conscientious objection due to the stigmas associated with sexual violence and their RS on abortion. As it deals with the circulation of social thought in certain groups, it is understood that SRT is pertinent to studying the abortion stigma that permeates the work of doctors who deal with legal abortion. The aim here is to find out the SR about legal abortion of pregnancies resulting from sexual violence for gynecologists and obstetricians, based on their practices in relation to conscientious objection. Two complementary studies were carried out. The first, with a documentary design, observational nature and descriptive quantitative approach, outlined the sociodemographic profile of pregnant patients seen at a referral service for cases of sexual violence. The second, with an analytical qualitative approach, aimed to find out the SR on abortion for gynecologists and obstetricians, based on conscientious objection, and their understanding of the risk factors for sexual violence. Study I showed a prevalence of black, young, single women with low levels of schooling, who had been raped by men they knew in a domestic environment, and who sought the service spontaneously after discovering their pregnancy and deciding to have an abortion. The results of Study II showed a tendency to blame the victim for the violence suffered, through moral and religious judgments, and that conscientious objection occurred as a form of punishment for the patients, based on the shared SR of abortion as a crime and a sin. We also conclude that there is a relationship between the SR formed about abortion and social thinking about the black population, reflecting the mistrust and lack of recognition of black women as the group most affected by sexual violence